Pengaruh Pelatihan (Bimbingan Teknis Implementasi Program Peningkatan Mutu) terhadap Pengetahuan dan Ketepatan Pengisian Dokumen Mutu Keperawatan di RSIA Puri Bunda - Nuthea, Merry (Jurnal Ilmiah Administrasi Publik, 2018)
Hospital’ s document is one of the most important elements during assessment of accreditation. The report of the quality of hospital care is one of the documents which assessed by the surveyor. In RSIA Puri Bunda, specifically the nurses have problem with inaccuracy of analyze the document which can lead to take a wrong decisionThe purpose of this study to identify the differences before and after the implementation of workshop and to know the relation between knowledge with the accuracy of analyzing and writing the quality report. According to the result, it showed that there is the difference before and after the implementation of the workshop with the probability < alpha = 0, 05. Meanwhile, even though the result was not significant which is 0,8%. the influence test showed that the knowledge has influence in the accuracy of analyzing and writing the quality report. The conclusion of this study is the workshop can increase the knowledge and accuracy of analyzing and writing the quality report.